Dual functions of silver nanoparticles in F9 teratocarcinoma stem cells, a suitable model for evaluating cytotoxicity- and differentiation-mediated cancer therapy - Han JW (Dove Medical Press, 2017)
Jae Woong Han, Sangiliyandi Gurunathan, Yun-Jung Choi, Jin-Hoi Kim Department of Stem Cell and Regenerative Biotechnology, Humanized Pig Research Center (SRC), Konkuk University, Seoul, Republic of Korea Background: Silver nanoparticles (AgNPs) exhibit strong antibacterial and anticancer activity owing to their large surface-to-volume ratios and crystallographic surface structure. Owing to their various applications, understanding the mechanisms of action, biological interactions, potential toxicity, and beneficial effects of AgNPs is important. Here, we investigated the toxicity and differentiation-inducing effects of AgNPs in teratocarcinoma stem cells. Materials and methods: AgNPs were synthesized and characterized using various analytical techniques such as UV–visible spectroscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy, and transmission electron microscopy. The cellular responses of AgNPs were analyzed by a series of cellular and biochemical assays. Gene and protein expressions were analyzed by reverse transcription-quantitative polymerase chain reaction and western blotting, respectively. Results: The AgNPs showed typical crystalline structures and spherical shapes (average size =20 nm). High concentration of AgNPs induced cytotoxicity in a dose-dependent manner by increasing lactate dehydrogenase leakage and reactive oxygen species. Furthermore, AgNPs caused mitochondrial dysfunction, DNA fragmentation, increased expression of apoptotic genes, and decreased expression of antiapoptotic genes. Lower concentrations of AgNPs induced neuronal differentiation by increasing the expression of differentiation markers and decreasing the expression of stem cell markers. Cisplatin reduced the viability of F9 cells that underwent AgNPs-induced differentiation. Conclusion: The results showed that AgNPs caused differentially regulated cytotoxicity and induced neuronal differentiation of F9 cells in a concentration-dependent manner. Therefore, AgNPs can be used for differentiation therapy, along with chemotherapeutic agents, for improving cancer treatment by targeting specific chemotherapy-resistant cells within a tumor. Furthermore, understanding the molecular mechanisms of apoptosis and differentiation in stem cells could also help in developing new strategies for cancer stem cell (CSC) therapies. The findings of this study could significantly contribute to the nanomedicine because this study is the first of its kind, and our results will lead to new strategies for cancer and CSC therapies. Keywords: silver nanoparticles, teratocarcinoma stem cells, cell viability, cytotoxicity, differentiation, cancer therapy